The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1021/la3021113
|View full text |Cite
|
Sign up to set email alerts
|

Simple, Reversible Emulsion System Switched by pH on the Basis of Chitosan without Any Hydrophobic Modification

Abstract: Chitosan without hydrophobic modification is not a good emulsifier itself. However, it has a pH-tunable sol-gel transition due to free amino groups along its backbone. In the present work, a simple reversible Pickering emulsion system based on the pH-tunable sol-gel transition of chitosan was developed. At pH > 6.0, as adjusted by NaOH, chitosan was insoluble in water. Chitosan nanoparticles or micrometer-sized floccular precipitates were formed in situ. These chitosan aggregates could adsorb at the interface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
151
1
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(172 citation statements)
references
References 63 publications
10
151
1
6
Order By: Relevance
“…Oil was added to the chitosan solutions at pH 4 and followed by a pH adjustment to pH > 6 and upon subsequent homogenization O/W Pickering emulsions were formed. One of the most interesting findings in this work is the reversibility of this emulsion system; reversion was repeated more than five times by the alternate addition of HCl and NaOH [59].…”
Section: Emulsification Properties Of Chitosanmentioning
confidence: 80%
See 1 more Smart Citation
“…Oil was added to the chitosan solutions at pH 4 and followed by a pH adjustment to pH > 6 and upon subsequent homogenization O/W Pickering emulsions were formed. One of the most interesting findings in this work is the reversibility of this emulsion system; reversion was repeated more than five times by the alternate addition of HCl and NaOH [59].…”
Section: Emulsification Properties Of Chitosanmentioning
confidence: 80%
“…Chitosan is usually not mentioned in the group of polysaccharides with good emulsification properties, but several studies have shown that chitosan can in fact act as the sole emulsifier and produce emulsions of acceptable stability [55][56][57][58][59][60].…”
Section: Biopolymer Emulsifiersmentioning
confidence: 99%
“…Recently, the synthesis and application of novel stimuli-responsive micro-particles as an emulsifier for the controlled formation of Pickering emulsions have attracted increasing attention (Liu et al, 2012). Among available stimuli, pH is a convenient method to manipulate emulsions.…”
Section: Ph Responsive Behavior Of Toluene/water Emulsions Stabilizedmentioning
confidence: 99%
“…Among available stimuli, pH is a convenient method to manipulate emulsions. However, most of these pH-responsive emulsifiers usually require tedious synthesis labor (Liu et al, 2012). In the present work, the pH sensitive behavior of Pickering emulsions stabilized by palygorskite was investigated during the in-situ preparation of toluene/water emulsions by using water with different pH values.…”
Section: Ph Responsive Behavior Of Toluene/water Emulsions Stabilizedmentioning
confidence: 99%
“…Although scientists have tried using naturally occurring materials, such as viruses (Russell et al, 2005) and protein particles (Fujii et al, 2009), to stabilize Pickering emulsions, the large-scale application of these materials will be limited by their high cost and complicated synthesis process. Therefore, much interest has been shown for investigation of particulate emulsifiers using natural macromolecular polysaccharides such as chitosan, cellulose, and starch (Kalashnikova, Bizot, Cathala, & Capron, 2011;Liu, Wang, Zou, Wei, & Tong, 2012;Tan et al, 2012).…”
Section: Introductionmentioning
confidence: 99%